2016
DOI: 10.15616/bsl.2016.22.2.37
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Oncogenic Human Papillomavirus Genotypes at High Grade Cervical Lesions above CIN 2 Grade with Histological Diagnosis

Abstract: High risk human papillomavirus (HR-HPV) is major risk factor for uterine cervical cancer. There are approximately 15 types of HR-HPV. Liquid based cytology samples (116 samples) with high grade cervical lesions belonging to cervical intraepithelial neoplasia (CIN) 2, CIN 3, carcinoma in situ (CIS) and squamous cell carcinoma (SCC) were used after histologic confirmation. HR-HPV genotype assay was conducted using DNA chips. The HR-HPV infection rate was 81.9% with SCC samples showing the highest HR-HPV infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…A similar observation was reported in studies from two African countries-Malawi and Ghana having multiple HPV infections that accounted for 54.0% and 52.2% respectively [19, 25]. Lower rates of multiple HPV infection were reported in studies from Croatia [11], Serbia [15], India [17], Thailand [18], Ibadan Nigeria [21], Pakistan [35], Republic of Benin [41], USA [42], Brazil [43], Korea [44] and Sri Lanka [45]. Although most of the studies from Africa have observed multiple HPV infections, the finding in this study was as expected.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…A similar observation was reported in studies from two African countries-Malawi and Ghana having multiple HPV infections that accounted for 54.0% and 52.2% respectively [19, 25]. Lower rates of multiple HPV infection were reported in studies from Croatia [11], Serbia [15], India [17], Thailand [18], Ibadan Nigeria [21], Pakistan [35], Republic of Benin [41], USA [42], Brazil [43], Korea [44] and Sri Lanka [45]. Although most of the studies from Africa have observed multiple HPV infections, the finding in this study was as expected.…”
Section: Discussionsupporting
confidence: 75%
“…However, most studies have identified that multiple HPV types exhibit synergism and additivity and were associated with persistent infection, higher risk of disease progression, disease severity and poor survival [17, 43, 47, 48]. Conversely, Salazar et al [42] and Wang et al [50] have shown no significant difference between single and multiple HPV infection, but a reduced rate of high-grade cervical lesions. Intergenotypic competition or effective immune response has been suggested as a possible mechanism for a reduced rate of high-grade cervical lesions in multiple HPV infections [42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HPV screening test is done by molecular diagnostic technology such as PCR, real-time PCR, and NASBA method using HPV DNA or RNA [17][18][19][20]. Especially, real-time PCR is more sensitive and specific molecular diagnostic method to detect live HPV in patients compared to other methods [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%